Pengaruh Insider Ownership dan Leverage Terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderasi - Wibowo, Andi Satrio; Yuniningsih, Yuniningsih (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2022)
The purpose of this study is to analyze the effect insider ownership and leverage on firm value and use dividend policy to strengthen and weaken the effect independent variable. The method of determining the sample in this study is purposive sampling. The indicators for determining the sample are (1) all property, real estate dan construction companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019, (2) companies that consistently report consolidated financial statements (3) companies are distributed insider ownership (4) Companies that distributed cash dividends to shareholders. Hypothesis testing using multiplier regression analysis and moderated regression. The Result of this study prove that insider ownership has a positive effect on firm value, leverage has no significant effect on firm value, dividend policy can strengthen the relationship between insider ownership and firm value and dividend policy cannot moderated relevant leverage on firm value.